COSTING METHODS FOR SUPPLY CHAIN MANAGEMENT - Anna Surowiec (European Scientific Journal, ESJ, 2013)
Today's organizations, operating in an increasingly competitive conditions, are characterized by a network of relationships with suppliers and customers. Thus, the key resources, being a source of competitive advantage, are located not only within the organization but are part of network relationships. The most important task of managers is to achieve supply chain cost efficiency while maintaining high flexibility. This article focuses on the potential role that management accounting information can play in supply chain management. It describes key methods that can be used in practice to implement management accounting practices that facilitate effective supply chain management.